The wildelings : a novel - Harding, Lisa (HarperVia, an imprint of HarperCollinsPublishers, 2025)
"Jessica and Linda have been best friends since the first day of school. Both girls are from very different broken homes--and beautiful, wilful Jessica has always ensured their survival. Now eighteen, the two have come to Wilde--an elite university in the heart of Dublin, far away from their troubled childhoods. Jessica thrives immediately, and, with the faithful Linda at her side, finds herself at the heart of a new circle of friends. But then Mark enters the picture. A philosophy student a few years older than them, he has strange and compelling ideas about self-discovery. When Linda and Mark start dating, Jessica is disturbed by the change in her friend--and how quickly she seems to have fallen under the charismatic man's control. It turns out that Mark's influence is not limited to Linda alone; and Jessica soon finds out that her whole group of friends are keeping secrets for him... and it will culminate in ways that will change their lives forever"--